2015
DOI: 10.1590/1980-5497201500040009
|View full text |Cite
|
Sign up to set email alerts
|

Fatores que contribuem para preocupação com a imagem corporal de estudantes universitárias

Abstract: Medication use due to studies, academic performance, economic class and body mass index significantly contribute to body image concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…Concerning the Mozambican students, those that use medication for body change and have higher BMI showed greater body weight concerns. Silva et al [16] indicated a significant influence of students’ self-reported academic performance, frequency of medication use because of studies, SES, and BMI in body concerns of Brazilian female college students. Similar results were found in Martins et al [38], Razak et al [22], Fan et al [17], and Shunk and Birch [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the Mozambican students, those that use medication for body change and have higher BMI showed greater body weight concerns. Silva et al [16] indicated a significant influence of students’ self-reported academic performance, frequency of medication use because of studies, SES, and BMI in body concerns of Brazilian female college students. Similar results were found in Martins et al [38], Razak et al [22], Fan et al [17], and Shunk and Birch [37].…”
Section: Discussionmentioning
confidence: 99%
“…The literature highlights that feelings of academic pressure and insecurity [1416], use of medication because of studies, use of supplements and medication for body change [1619], socioeconomic status (SES) [20], and body index mass (BMI) [16,21] affect body weight concerns. Further, some studies [21,22] suggest that female college students, especially younger ones, are particularly susceptible to body weight concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Confirmatory factor Analysis (CFA) was conducted with the collected data in 2013 to certify the elementary factors produced by Exploratory Factor Analysis (EFA) with the collected data in 2009 using Comparative Fit Index (CFI), Tucker Lewis Index (TLI) and RMSEA. These indices' criteria must be met for a satisfactory fit model: (1) Chi-square/df ratio should be between 1 and 5; (2) CFI and TLI must approach 1 [21] , [22] ; (3) the Standardized Root Mean Square Residual (SRMR) must be less than 0.1; (4) RMSEA should be up to 0.09 with 90% confidence interval values below 0.1 [22] . A multivariate linear regression was used to predict the factors associated with depression.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13][14][15][16] Este resultado pode ser justificado pelo fato de, no presente estudo, a maioria de universitários participantes serem mulheres. Pois o desejo por uma silhueta menor do que a atual tem sido relatada frequentemente na literatura e, trata-se normalmente de uma característica associada a mulheres enquanto os homens apresentam, em geral insatisfação pela magreza, desejando uma silhueta maior, representando um ideal de corpo com maior hipertrofia muscular.…”
Section: 31-33unclassified